HUMAN RIGHTS IN KAZAKHSTAN AND THE UNITED KINGDOM: - Castellino, J.; Sairambayeva, Zh. T.; Baimagambetova, Z. M.; Otynshiyeva, A. A. (Farabi Journal of Social Sciences, 2020)
The article examines the human rights issues based on the experience of the Republic of Kazakhstan and the United Kingdom. A comparative analysis of the scientific views of domestic and foreign scientists; reveals the problematic aspects of protecting human rights. In the era of globalization, the role of the human rights in solving urgent problems of human civilization is growing. In recent years, dramatic changes have occurred in the global legal system and the legal system of Kazakhstan. These changes will serve as the basis for the protection, enforcement and development of human rights. On the one hand, it is a process of integration and regionalization based on world globalization, on the other hand, domestic political and liberal reform processes in Kazakhstan. The main aim of the articles in the context of globalization, to do a comparative analysis of human rights in the Republic of Kazakhstan and in the UK, to develop further recommendations for improving the human rights legislation of the Republic of Kazakhstan.